Roles of zinc and zinc transporters in development, progression, and treatment of inflammatory bowel disease (IBD) - Mitchell, S. B.; Aydemir, T. B. (Frontiers in Nutrition, 2025)
The inflammatory bowel diseases (IBD), including Crohn’s Disease and Ulcerative Colitis, are chronic, incurable disorders of the gastrointestinal tract. These multifactorial diseases pose an enormous burden on patients, clinicians, and public health systems worldwide. Zinc (Zn) is an essential micronutrient that is required for a wide variety of functions critical to maintaining gastrointestinal health. Zn homeostasis is facilitated by the SLC39/ZIP and SLC30/ZnT families of solute carrier proteins, which collectively distribute Zn with subcellular specificity. Disruptions in Zn homeostasis can have substantial impacts on health, as recent years have seen Zn transporters become increasingly recognized for their importance in health and disease. Although dietary Zn deficiency is rare in the United States, Zn deficiency is common among IBD patients. Disruptions in Zn homeostasis have also been shown to play a role in the progression of IBD. Despite these links, Zn supplementation trials in IBD have shown inconsistent results. This review focuses on the role of Zn and Zn transporters in the development, progression, and treatment of IBD, as well as discussing the challenges and potentially promising future of the study of Zn and Zn transporters in precision health.